DEVELOPING THE LEARNING MATERIALS OF BIOTECHNOLOGY SUBJECT BASED ON STUDENTS’ NEED AND CHARACTER OF NUSANTARA PGRI UNIVERSITY OF KEDIRI - Farida Nurlaila Zunaidah; Mohamad Amin (University of Muhammadiyah Malang, 2016)
Various applications and utilization of biotechnology are very important to be introduced early. Introducing biotechnology through levels of education can be done by transferring science to students. Transferring knowledge through lectures activities are often experience constraints, one of them is that there is no adequate source of learning materials available. The research aimed todevelop a teaching materials of biotechnology course which is suited to the students’ necessary. The method used was 4Ddevelopment model which was adopted from Thiagarajan, et al (1974). The model contains four stages, i.e. define, design, develop, and deploy. Data collection techniques was using validation questionnaires for experts, individual test and small-scale trials. Data analysis results show that the average results of validation and testing were categorized as “eligible” with “good”predicate , based on the Eligibility Level Criteria and Product Revise table. Theproduct has an advantages and disadvantages which still needed to be revised.